Back to basics: likelihood ratios for olive and grass pollen specific IgE in seasonal allergic rhinitis - Manzanares, Bárbara; González, Rafael; Serrano, Pilar; Navas, Ana; Alonso, Corona; Fernandez, Lourdes; Jurado, Aurora; Moreno-Aguilar, Carmen (Frontiers in Allergy, 2023)
ratio (LR) of 10.08 set for grass allergy. Olea sIgE showed the best AUC for the diagnosis (0.950). The optimal cut-off for diagnosis was 2.41 kUA/l. A value of 6.49 kUA/l was associated with a positive LR of 9.98 to confirm olive pollen allergy. In regard to immunotherapy, Ole e 1 sIgE showed the best AUC (0.860). The optimal cut-off was 14.05 kUA/l. Ole e 1 sIgE value of 4.8 kUA/l was associated with a 0.09 negative LR to exclude olive AIT indication.The sIgE cut-offs found in this population under high olive and grass allergenic pressure reduce the gap between sensitization and clinical allergy, providing a new tool for the diagnosis of seasonal allergic rhinitis/asthma and helping to discriminate patients who will benefit from AIT.